MEMBANGUN FINANCIAL WELL BEING MELALUI FINANCIAL LITERASI, LOCUS OF CONTROL DAN FINANCIAL PLANNING PADA KARYAWAN PTPN 4 REGIONAL 2 KEBUN SAWIT SEBERANG - Khairani, Khairani; Tamba, Riris Debora (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the effect of financial literacy and locus of control on financial well-being with financial planning as a mediating variable among employees of PTPN IV Kebun Sawit Seberang. This study uses a quantitative approach with an explanatory research design. Data were collected through a survey using a five-point Likert scale questionnaire administered to 80 respondents selected through convenience sampling. Data analysis was performed using SmartPLS 3 software to test validity, reliability, and relationships between variables through a structural model. The results showed that financial literacy and locus of control had a positive and significant effect on financial well-being. However, financial planning did not have a direct effect on financial well-being. Nevertheless, financial planning was found to moderate the relationship between financial literacy and financial well-being, which means that financial planning can strengthen the effect of financial literacy on financial well-being. Conversely, financial planning does not moderate the relationship between locus of control and financial well-being. These findings emphasize the importance of improving financial literacy and self-control in supporting individual financial well-being, as well as the need for consistent financial planning to have a real impact on employees' financial conditions.